Enhancing Safety and Health Facilities for Construction Workers: An Empirical Study of Lamahi Ghorahi Tulsipur and Sahajpur Boktan Dipayal Road Project - Yadav, A.; Mishra, A. K.; Parajuli, K. P.; Mishra, A. K. (Journal of Lumbini Engineering College, 2024)
This field-based empirical research employs a combination of quantitative and qualitative approaches to address a practical problem related to the safety and health of construction workers. The study utilizes data collected through observation checklists, Key Informant Interviews (KII), and questionnaires distributed to project-related respondents and design professionals not directly associated with the project. The research examines the occurrence of accidents, which were predominantly of a minor nature, and identifies the critical safety and health measures required to address the challenges faced by workers on construction sites. These measures encompass safe drinking water, first-aid equipment, sanitary facilities, provision of Personal Protective Equipment (PPE), and the training of casual workers in safety procedures. The study also evaluates the extent of safety and health provisions within contract documents, contrasting them with the inclusion of staff and worker insurance. Additionally, the research explores the impact of hazard identification, health facilities, and safety provisions on project performance. The study underscores the need to disseminate knowledge about safety and health through training courses, orientation sessions, awareness programs, pictorial representation, and online forums. The safety and health status of construction sites can be significantly improved by implementing the recommendations presented in the final section of this research. It is further recommended that a brief safety and health briefing of five to ten minutes be conducted each morning before work commences. The primary objective of safety and health programs is to prevent workplace injuries, illnesses, and fatalities, ultimately mitigating the suffering and financial burdens these incidents impose on workers, their families, and employers. This research offers empirical insights into practical solutions for enhancing safety and health facilities for construction workers, emphasizing the importance of proactive measures and awareness programs in promoting a safer and healthier work environment.